TRANSESTERIFIKASI MINYAK BIJI KARET (Hevea brasiliensis) MENGGUNAKAN KATALIS HETEROGEN CANGKANG KEPITING LIMBAH SEAFOOD TERMODIFIKASI K2O - Astuti, N. K. D.; Simpen, I N.; Suarsa, I W. (Jurnal Kimia (Journal of Chemistry), 2019)
The CaO heterogeneous catalysts can be prepared by CaCO 3 calcination process, with one source of CaCO 3 being a crab shell from seafood waste. The preparation of the heterogeneous catalyst was successfully carried out by modification with KOH using a wet impregnation method at 800 o C for 5 hours. The purpose of this research is to determine the physical and chemical characteristics of heterogeneous catalyst of K 2 O-modified crab shell and to examine the heterogeneous catalyst of K 2 O-modified shells in converting rubber seed oil into biodiesel. The results showed that the lowest basic alkalinity possessed without modified catalyst (1.0428 mmol g -1 ) and the highest alkali possessed potassium-modified catalyst (1.8314 mmol g -1 ). Characterization of specific surface area of ??crab shells without and with modified K 2 O were relatively the same. The surface morphology of the catalyst without and K 2 O modified was uniform. The catalyst examination results for conversion of rubber seed oil ( Hevea brasiliensis ) to biodiesel, the optimum catalyst concentration of 3% and the molar ratio of oil:methanol of 1:9 capable converting to biodiesel with the yield of 91.05%. The content of biodiesel were stearic methyl ester, linoleic methyl ester, linolenic methyl ester, and palmitic methyl ester.